Legal Review on Consumer Protection in E-Commerce Transactions - Cahyo Rosanto, Tibar; Komala Sari, Surti; Supriyadi, Yodi; Rahman, Alip; Dikrurahman, Diky (Devotion : Journal of Research and Community Service, 2024)
The use of e-commerce in trade has had a big impact on Indonesian society, especially in terms of very important legal issues. Legal protection in e-commerce is crucial to protect consumers who make buying and selling transactions via the internet. This development is driven by high demand and acceptance from the public, as evidenced by the emergence of various online stores such as Kaskus, Tokopedia, Bukalapak, Shopee, and Lazada. Rapid advances in technology have changed the method of buying and selling from physical stores to online transactions via the internet. E-commerce, as an information technology innovation, allows consumers to make transactions with just the touch of a finger without having to leave the house. However, the variety of e-commerce platforms available increases the potential for legal issues in online transactions. This research aims to understand how to legally protect consumers and help them if losses occur in e-commerce transactions. The method used is a normative approach, by reviewing literature and secondary data related to consumer legal protection in e-commerce transactions.